El diseño de una vida, María de Jesús Tomellín, el “Lirio de Puebla”. Libros, devociones y agentes culturales, siglos XVII y XVIII - Loreto López, Rosalva (El Colegio de México, A.C., 2023)
This article suggests an approach to the complex process of the beatification of the nun María de Jesús Tomellín through a study of the publishing history of her four hagiographies. This will allow them to be analyzed as cultural agents, both in their intentions as well as in the social and political networks that were articulated in each of their printings in New Spain and Europe. Each one of these texts captured adaptations to the beatification policies imposed by the Holy See over the course of an eighty-year period. A comparative study of their printings also allows us to analyze their internal organicity and reveals the adaptations undergone by their publishing formats, as well as the importance of their circulation and their transition from being promotional to devotional books. In this sense, it’s possible to perceive the advances introduced into the design and printing of these works between one century and another. As a result of this “divine enterprise,” the venerable Pueblan nun was given a face and a specific iconography.